2009
DOI: 10.2528/pierc09010508
|View full text |Cite
|
Sign up to set email alerts
|

Design of Metamaterial Multilayer Structures as Frequency Selective Surfaces

Abstract: The reflection and transmission coefficients of multilayer structures are computed by the Transmission Line Transfer Matrix Method (TLTMM) and it is shown that metamaterials (MTMs) act as frequency selective surfaces (FSSs). Several examples of multilayer structures are analyzed, which are composed of combination of common materials and MTMs with dispersion relations. Interesting and uncommon behaviors are observed for MTMs. Novel applications are treated by TLTMM and a matrix method. The physical realizabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…10 with tan δ = 1.0e−3 at f = 96.0092 GHz as an example, the transmission coefficient of the single layer FSS is T 2 = 8.22e − 06, while the dielectric loss is 6.24e − 04. From (19) it is assumed that there is no dielectric loss when considering conductor losses, and vice versa. The foam is assumed to be lossless.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…10 with tan δ = 1.0e−3 at f = 96.0092 GHz as an example, the transmission coefficient of the single layer FSS is T 2 = 8.22e − 06, while the dielectric loss is 6.24e − 04. From (19) it is assumed that there is no dielectric loss when considering conductor losses, and vice versa. The foam is assumed to be lossless.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…These structures are used in anti-reflection coatings, radar absorbing structures, and filters [1][2][3]. Alternating layers of double positive (DPS) and double negative (DNG) materials are used to show transmission tunneling [4].…”
Section: Introductionmentioning
confidence: 99%
“…Liu and Behdad demonstrated that the problem of EM wave tunneling through cascaded epsilon-negative metamaterial and double positive material barrier structure is analogous to the classical problem of coupled-resonator microwave filters [5]. In recent studies on multilayered structures, researchers have been using integer dimension substrate [1][2][3][4][5][6]21]; this means that the effect of dimension on the characteristics of structures was not considered. This research has been carried out to further include the parameter of dimension and see its effect on the characteristics of the multilayered structures, because not every object that exists in this universe can be modeled with Euclidean geometry (integer dimension).…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] As it is well known that metamaterials are composed of subwavelength unit cells, it is convenient to design FSS using the concept of metamaterial. [10][11][12][13] As an alternative to metallic FSS, dielectric materials can be used to design and fabricate FSS or filters. Actually, the study of employing dielectrics in filters design may date back to decades ago.…”
Section: Introductionmentioning
confidence: 99%